Graphite-supported ultra-small copper nanoparticles – Preparation, characterization and catalysis applications. (November 2015) - d'Halluin, Martin; Mabit, Thibaud; Fairley, Neal; Fernandez, Vincent; Gawande, Manoj B.; Le Grognec, Erwan; Felpin, François-Xavier
Abstract: A convenient preparation of graphite-supported ultra-small copper nanoparticles (Cu NPs) has been developed. Ultra-small Cu NPs, generated by reduction of Cu(OAc)2 with H2, were well dispersed onto the graphite support and possess a very narrow distribution in size, ranging from 1.6 to 2.6 nm. The catalytic activity of these ultra-small graphite-supported Cu NPs was evaluated for the Meerwein arylation of pyrroles and the multicomponent synthesis of 1, 2, 3-triazoles via click reaction.